2022
DOI: 10.1098/rsif.2022.0212
|View full text |Cite
|
Sign up to set email alerts
|

The physical properties of the stick insect pad secretion are independent of body size

Abstract: Many insects use adhesive organs to climb. The ability to cling to surfaces is advantageous but is increasingly challenged as animals grow, due to the associated reduction in surface-to-volume ratio. Previous work has demonstrated that some climbing animals overcome this scaling problem by systematically altering the maximum force per area that their adhesive pads can sustain; their adhesive organs become more efficient as they grow, an observation which is also of substantial relevance for the design of bioin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
(61 reference statements)
0
7
0
Order By: Relevance
“…Firstly, due to the high viscosity, it was not possible to collect a large amount of tarsal fluid using self-pulled glass needles and a micromanipulator, and secondly, the tarsal fluid was distributed over the surface in numerous fine droplets, and thus, there was no sufficient initial volume (own observations). Nevertheless, some results regarding the physical properties of the tarsal secretion of Phasmatodea were recently provided in [ 35 ]. They measured the contact angle (°) and dewetting speed (µm/s) of the tarsal secretion of phasmids with different body sizes and showed that the surface tension and viscosity of the fluid on glass are independent of the body size [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, due to the high viscosity, it was not possible to collect a large amount of tarsal fluid using self-pulled glass needles and a micromanipulator, and secondly, the tarsal fluid was distributed over the surface in numerous fine droplets, and thus, there was no sufficient initial volume (own observations). Nevertheless, some results regarding the physical properties of the tarsal secretion of Phasmatodea were recently provided in [ 35 ]. They measured the contact angle (°) and dewetting speed (µm/s) of the tarsal secretion of phasmids with different body sizes and showed that the surface tension and viscosity of the fluid on glass are independent of the body size [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is then released through channels onto the substrate [ 25 , 26 ]. The chemical compositions and functions of the tarsal fluids of insects have been investigated in several studies during the past decades (e.g., [ 2 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]). A chemical analysis of the tarsal secretion was conducted for representatives of different insect groups, such as Diptera [ 36 ], Hymenoptera [ 37 , 38 ], Coleoptera [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ], Orthoptera [ 28 , 47 ], and Blattodea [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…The hydrophilic properties of the leaves enhanced adhesion of Phasmatodea species studied [ 49 ]. Phasmatodea have adhesive secretions [ 50 , 51 , 52 , 53 ] that could be positively affected by the hydrophilicity of the substrate [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Surface tension is another important physical property of a bioadhesive fluid, as the capillary forces associated with it can be dominant at small spatial scales. However, to our knowledge, this property so far has been measured only indirectly through contact angle measurements [ 58 , 99 , 100 ]. Contact angle, or the angle between the substrate and fluid meniscus, quantifies the ‘wettability’ of a fluid on a substrate.…”
Section: Discussionmentioning
confidence: 99%
“…Contact angle, or the angle between the substrate and fluid meniscus, quantifies the ‘wettability’ of a fluid on a substrate. For insects and tree frogs, this contact angle has been found to be quite small (~10°) on a wide variety of substrates, so the adhesive fluid appears to be highly wetting regardless of substrate chemistry [ 58 , 99 , 100 ]. Recent studies of insects have made assumptions of the surface tension of the fluid given that it is comprised of hydrocarbons [ 101 , 102 ].…”
Section: Discussionmentioning
confidence: 99%